The SMOL case: the SoDIS approach to teaching "electronic transactions security" - Petrova, K.; Sinclair, R. (AUT University, 2006)
There is an increasing vulnerability of businesses to attacks on their systems, which has given rise to an increased interest in areas such as information security and risk management. In the project discussed here, the methodology developed for SoDIS (Software Development Impact Statement) was applied to evaluate risks related to business stakeholders, and to justify a security solution. A teaching case study was used. This report provides an update on the project, as presented at the 8th SoDIS Symposium (July 2006) in Wellington, New Zealand.